The Influence Of Work Motivation, Work Discipline And Work Environment On Employees’ Job Satisfaction At PT. Samudera Perdana Selaras - Efi - Jayanti; Rara RirinBudi Utaminingtyas; Umar - Farouk (Politeknik Negeri Semarang, 2020)
The objectives of this research were to analyze the influence of work motivation, work discipline and work environment on employees’ job satisfaction at PT. Samudera Perdana Selaras. The methods of data collection used were questionnaire and interview. The technique of analysis used in this research was multiple linear regression analysis. The sample of this research consisted of 62 respondents and analytical method used were validity test, reliability test, classic assumption test, multiple linear regression, coefficient determination, t test and F test. The result of multiple linear regression analysis could be shown by the regression equation Y = 0.837 + 0.382 X1 + 0.267 X2 + 0.239 X3. The coefficient determination of this research was 53.9%, which meant that the contribution of work motivation, work discipline and work environment on employees’ job satisfaction was 53.9% and the remaining 46.1% was influenced by other variables which were not examined in this research. The result of this research shows that work motivation, work discipline and work environment had positive and significant influence on job satisfaction.